ANALISIS PIUTANG TAK TERTAGIH TERHADAP TINGKAT PERPUTARAN PIUTANG PADA CV SURYAMAS DI KABUPATEN OKU - Sulistiawan, Tessa; Bramana, Sally Maria; Anwar, Yuniarti; Yunsepa, Yopi (Jurnal Ecoment Global, 2021)
This study is entitled Analysis of Uncollectible Accounts Receivable Turnover Rate at CV Suryamas in OKU Regency, with the formulation of the problem is how to analyze uncollectible accounts on the turnover rate of accounts receivable at CV Suryamas in OKU Regency. The method used in this research is descriptive method. This method is used by means of research prioritizing systematic observation of existing activities to obtain appropriate and targeted results by using the analysis tools for the bad debts ratio and the accounts receivable turnover ratio. The results showed that the risk of uncollectible receivables from CV Suryamas in 2015-2019 was 0.11%. While CV Suryamas' receivables turnover in 2015-2019 was seen from the average collection ratio of 121.78%. When viewed, the ratio of non-performing receivables is 0.11%, which means that there is less risk of uncollectible receivables and the average collection ratio reaches 100%. Based on the analysis of the uncollectible accounts receivable ratio to the CV Suryamas receivable turnover ratio in OKU Regency during 2015-2019, it shows that the management of uncollectible accounts has been strived to run properly. This can be seen from the ratio of arrears whose value is less than 3% and the collection ratio reaching 100%, although the receivable turnover ratio has an impact on the inefficient use of business capital and the average collection period ratio also estimates bad debts at 60%.